PENGARUH PELATIHAN FARTLEK DAN OBSTACLE RUN TERHADAP DAYA TAHAN KARDIORESPIRASI - Riza Sri Purwanthi, Ni Luh (Jurnal Ilmu Keolahragaan Undiksha, 2013)
The research was conducted in order to figure out the effect fartlek training and obstacle run towards cardiorespiratori endurance. This research was quasi-experimental with the design uses the modifide randomized pre-test post-test control group design. Sampel used was son student of class X of Â SMAN 1 Amlapura school year 2012/2013 as many 30 people. Cardiorespiratory endurance was measured with a 2.4 kilometer test. Analysis of the data used in this research with One Way ANOVA test with SPSS 16.0 the results variable fartlek training group and obstacle run training group with a significance Î± (0.000 < 0.05). Followed by Least Significant Different (LSD) tes for comparison, the fartlek training (-1.57) is better than obstacle run training (-0.96). From these results it can be concluded that:(1) fartlek training have effect on cardiorespiratory endurance, (2)obstacle run training have effect on cardiorespiratory endurance. (3) there are difference effect on fartlek and obstacle run training, fartlek training is better than obstacle run trainingÂ  for cardiorespiratory endurance. Recommended for sports people use to fartlek training as alternative to improve cardiorespiratory endurance.